1998
DOI: 10.1080/095530098141609
|View full text |Cite
|
Sign up to set email alerts
|

The radioprotective effect of BBI is associated with the activation of DNA repair-relevant genes

Abstract: The radioprotective effect of the Bowman-Birk proteinase inhibitor was accompanied by elevated mRNA expression of repair-relevant genes prior to irradiation. Activation of the DNA-repair machinery induced by pre-treatment with BBI is one possible mechanism of the radioprotective effect of BBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
5
14
0
Order By: Relevance
“…Moreover, similar effects of P-Tyr and BBI could be identified by quantifying TP53 and CDKN1A protein levels after a preincubation with P-Tyr. As described for BBI [15], P-Tyr treatment also induced a significant stabilization of the TP53-protein in normal cells within 3 hr. Thus, the radioprotective effect of P-Tyr can be correlated with TP53 stabilization.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, similar effects of P-Tyr and BBI could be identified by quantifying TP53 and CDKN1A protein levels after a preincubation with P-Tyr. As described for BBI [15], P-Tyr treatment also induced a significant stabilization of the TP53-protein in normal cells within 3 hr. Thus, the radioprotective effect of P-Tyr can be correlated with TP53 stabilization.…”
Section: Discussionsupporting
confidence: 65%
“…Although the mechanism of radioprotection mediated by P-Tyr is not clear at present, we favor an analogy to the mechanism described for BBI [15], a stimulating effect on DNA-repair processes.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Purified soybean BBI and BBIC have been shown to inhibit the growth of LNCaP human prostate cancer xenografts in nude mice [72], and to decrease the growth, invasion and clonogenic survival of several human prostate cancer cells [73]. The effectiveness of soybean BBI in preventing the generation of activated oxygen species in prostate cancer cells [74] and in activating DNA repair through a p53-dependent mechanism has been reported [75]. More recently, BBIC has prevented the growth of prostate tumors in transgenic rats developing adenocarcinoma, most likely as a consequence of its antiproliferative activity via induction of connexin 43 expression [76,77].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Dittmann et al [81] showed that soybean BBI increased clonogenic survival after irradiation only in cells, either normal or transformed, having a wild-type p53 tumor suppressor gene. In a cell line with inducible expression of mutated p53, the radioprotective effect of BBI was only detected when the expression of the mutated p53 was switched off [75]. The activation of the DNA-repair machinery, induced by pre-treatment of fibroblastic cells with soybean BBI, suggests a possible BBI-mediated p53-dependent mechanism for radioprotection [82,83].…”
Section: Radioprotectionmentioning
confidence: 99%